India’s Contribution to Astronomy: Religious and Historical Background - Chatterjee, S.C. (SCHOOL SCIENCE, 2013)
In the dawn of civilisation people must have had a rudimentary knowledge of time and space, and all the ancient scriptures regarded the universe as consisting of a flat circular earth below and a heaven above through which the sun, the moon, and the stars move. Between them was the middle air, the abode of clouds and demigods. This cosmological picture was considerably changed by later religious thought, but the heavenly bodies were still worshipped as gods. In India the Rig Veda mentions that observatories were erected for astronomical purposes, as the practice of sacrificial rituals demanded the setting up of altars for religious performances, and therefore some astronomical knowledge was necessary for determining the propitious times and dates for periodic sacrifice. Thus some astronomical knowledge became necessary. Like the Babylonians and the Greeks, the Indian priests also kept detailed records of the rising and the setting of various celestial bodies, and thus established a kind of calendar; but without a clear idea of cause and effect. It was but natural that Divine Will was recognised, and the heavenly bodies were regarded as gods. A general belief in astrology was the natural consequence.